Personality and well-being in adolescents - Moreira, Paulo A. S.; Cloninger, C. Robert; Dinis, Liliana; Sá, Laura; Oliveira, João T.; Dias, Adelaide; Oliveira, Joana (Frontiers in Psychology, 2015)
Different profiles of the character dimensions of self-directedness, cooperativeness and self-transcendence result in different levels of wellbeing among adults. However, the description of the multidimensional character profiles on adolescents’ composite wellbeing remains unexplored. This study builds on previous studies with adults, and examines the linear and non-linear associations between the dimensions of the psychobiological model of personality and well-being in adolescents. Participated in this study 1540 adolescents (M=15.44, SD=1.731). Personality was assessed using the Temperament and Character Inventory (TCI). Well-being was evaluated in a composite perspective: satisfaction with social support, health-related quality of life, satisfaction with life and affect. Variable-centered and individual-centered analyses were performed.Self-directedness was strongly associated with all dimensions of affective and cognitive well-being regardless of the other two character traits. Cooperativeness was associated with non-affective well-being and with positive affect, but only when associated to elevation of Self-directedness and Self-transcendence. Self-Directedness and Cooperativeness explained 15.5% of the non-affective well-being variance. Self-Directedness and Self-Transcendence explained 10.4% of the variance in affective well-being. This study confirms the tendencies found in previous studies with adults from other societies, where each character dimension gives an independent contribution to well-being depending on the interactions with other Character dimensions. Also, this study highlights the importance of considering the non-linear influences of the character dimensions in understanding of adolescents’ wellbeing. These results have strong implications for youth positive mental health promotion, including for school-based policies and practices.